Characterization of Classical Flexural and Nummular Forms of Atopic Dermatitis in Childhood with Regard to Anamnestic, Clinical and Epidermal Barrier Aspects - Folke Hüppop; Stephan Dähnhardt-Pfeiffer; Regina Fölster-Holst (Medical Journals Sweden, 2022)
Nummular (coin-shaped) and classical (flexural) atopic dermatitis differ morphologically, but no other distinguishing features are known. The aim of this study was to determine differences and similarities of both variants in children. Detailed interviews, clinical examinations, biophysical measurements and electron microscopic analyses were performed on 10 children with nummular atopic dermatitis, 14 with classical atopic dermatitis and 10 healthy controls. Nummular atopic dermatitis affected more boys than girls and manifested less frequently within the first year of life than classical atopic dermatitis. Localization, distribution and morphology of the eczema varied more over time, and expression of keratosis pilaris was more severe in children with nummular atopic dermatitis. Both disease groups showed reduced hydration, increased transepidermal water loss and reduced intercellular lipid lamellae in lesional skin areas compared with non-lesional areas. These findings underline the separate classification of both variants. Further research is necessary to investigate the potential of diverging therapeutic approaches.